2004
DOI: 10.1590/s0001-37652004000400006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of yeast inorganic pyrophosphatase by organic solvents

Abstract: A number of application for enzymes in organic solvents have been developed in chemical processing, food related conversions and analyses. The only unsolved problem related to nonaqueous enzymology is the notion that enzymes in organic solvent are mostly far less active than in water. Therefore, studies concerning the mechanisms by which enzymes are inactivated by organic solvents would reveal a clear understanding of the structure-function relationship of this phenomenon. Here we analyzed the effects of a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…We demonstrate the use of HvPPA in a novel coupled assay to detect the PP i by-product released at reduced water activity (2 M NaCl) by ATP-dependent adenylation of the ubiquitin-like SAMP1 by the salt-loving E1-like enzyme UbaA. In contrast, current PPAs are inactivated in dose-dependent manner by salt and organic solvents (22)(23)(24). Our discovery of HvPPA and its function opens new possibilities for the hydrolysis of PP i and related compounds in systems which benefit from the use of high-ionicstrength compounds and/or organic solvents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrate the use of HvPPA in a novel coupled assay to detect the PP i by-product released at reduced water activity (2 M NaCl) by ATP-dependent adenylation of the ubiquitin-like SAMP1 by the salt-loving E1-like enzyme UbaA. In contrast, current PPAs are inactivated in dose-dependent manner by salt and organic solvents (22)(23)(24). Our discovery of HvPPA and its function opens new possibilities for the hydrolysis of PP i and related compounds in systems which benefit from the use of high-ionicstrength compounds and/or organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…PPAs are used routinely to quantify rates of reactions that release PP i as a byproduct, such as single nucleotide polymorphism (SNP) genotyping reactions (10-12), RNA synthesis by viral RNA-dependent RNA polymerases (13), and aminoacyl-tRNA synthetase activity (14,15). The advantage of PPA-coupled assays is that PPA hydrolyzes PP i to a product (2P i ) which is readily detected by colorimetric assay (16,17).PPAs that operate in a wide variety of organic solvents and salt concentrations are desirable in bioindustry to increase the solubility of hydrophobic substrates, allow for novel synthetic chemistry, alter substrate specificity, ease product recovery, and reduce microbial contamination (18)(19)(20)(21)(22)(23)(24). Biotechnological applications of solvent-tolerant PPAs can be envisioned in the biosynthesis of hydrophobic compounds derived from carbon skeletons such as cholesterol and rubber.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2). Interestingly, Grazinoli-Garrido and Sola-Penna (2004) have showed that the soluble yeast inorganic pyrophosphatase is also inactivated by several organic solvents (methanol, ethanol, propanol and acetone) depending on their hydrophobicity. This indicates that both the soluble and membrane bound pyrophosphatases seem to be highly sensitive to organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…Most PPAs are inactive at high salt concentrations and organic solvents, thereby limiting their usage. PPAs that function in a wide range of organic solvents and salt concentrations are desirable in bioindustry to increase the solubility of hydrophobic substrates, which has advantages toward synthetic chemistry, to alter substrate specificity, ease product recovery, and reduce microbial contamination (Grazinoli‐Garrido & Sola‐Penna, 2004).…”
Section: Lignocellulosic Components and Depolymerizationmentioning
confidence: 99%